2016
DOI: 10.2147/ppa.s96431
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ handling of a standardized medication plan: a pilot study and method development

Abstract: PurposeThe Action Plan for Medication Safety by the German Federal Ministry of Health introduced a standardized medication plan (MP), a printable document for the patient. The practical handling needs to be tested before the nationwide implementation in Germany. Therefore, the aims of our study were 1) to develop an instrument to evaluate the usage of the standardized MP, 2) to assess if patients can locate, and 3) understand important information. Moreover, we explored patients’ opinion and suggestions regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
0
14
0
3
Order By: Relevance
“…Diese sind: BMP entsprechend der da-rin vorgegebenen Dosierungsvorschriften exemplarisch Dosetten mit Placebos befüllen sollten. Als objektives Bewertungsinstrument wurde das "Evaluation Tool to test the handling of the Medication Plan" (ET-MP) entwickelt[7].…”
unclassified
“…Diese sind: BMP entsprechend der da-rin vorgegebenen Dosierungsvorschriften exemplarisch Dosetten mit Placebos befüllen sollten. Als objektives Bewertungsinstrument wurde das "Evaluation Tool to test the handling of the Medication Plan" (ET-MP) entwickelt[7].…”
unclassified
“…Our findings are especially relevant in Germany, where recently, after the start of our project, a federal standard medication list was introduced by law. Since October 2016 all patients taking at least 3 long-term drugs have the right to receive a medication list and physicians are obliged to issue the federal medication list in their practices [11]. Yet 1 year after the law came into force, the dissemination of the federal standard medication list was still poor: a survey among 324 health insured individuals showed that only 37% of those prescribed more than 3 drugs had received the federal standard medication list.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, medication lists issued by health care professionals may not meet patients' needs because they list information relevant to other health care professionals rather than giving adequate information to facilitate patients' self-support. For instance, in a study examining patients' understanding of a medication list, 35% of the participants were not satisfied with the design and 50% misunderstood the abbreviations given on the list [11].…”
Section: Introductionmentioning
confidence: 99%
“…Um diesen Aspekten entgegen zu wirken, sollte entsprechende Aufklärungsarbeit in der Bevölkerung in Bezug auf den Nutzen eines Medikationsplans erfolgen. Weiter sollten Maßnahmen angedacht werden, wie der Nutzen des Medikationsplans für Angehörige oder Dritte vermittelt werden kann, falls die medikamentösen Therapien für den Patienten selbst in der Umsetzung zu komplex sind [15,16]. Dieser wichtige Aspekt des Medikationsplans als Kommunikationsmittel, der auch in der Literatur beschrieben wird [4], wurde von einigen der befragten Bürger erkannt.…”
Section: Diskussionunclassified
“…Diese Diskrepanzen hängen mit objektiven Fakten wie Alter [10] oder Bildungsstand [12] zusammen. Andere Studien belegen Verständnisprobleme bei der Umsetzung des Medikationsplans [15,16]. Diese objektiven Ursachen für Diskrepanzen werden in der vorliegenden qualitativen Befragung ergänzt und weitere subjektive Kriterien aufgezeigt.…”
Section: Diskussionunclassified